Emotional Intelligence, Library Use and Academic achievement of University Students. Issue 1 (2nd January 2019) - Jan, Sajjad Ullah; Anwar, Mumtaz Ali
ABSTRACT: This paper, based on survey research, explores the association between emotional intelligence, library-use and academic achievement (GPA) among undergraduate university students in Pakistan. Participants ( N = 725) from the three different types of universities in Peshawar, Pakistan, namely University of Peshawar, University of Engineering and Technology, and University of Agriculture, responded to the Schutte's Emotional Intelligence scale and questions of library-use. Prior to the analysis, reliability of scale and normality of data were tested using SPSS (v.20). Results revealed that students with comparatively higher emotional intelligence score frequently visited their university library. A positive significant relationship was found between emotional intelligence and academic achievement (GPA) of these students. The researchers propose five levels of emotional intelligence on the basis of mean score and standard deviation. This work is an addition to the LIS literature that recommends library professionals to be aware of the importance of students' emotional intelligence in their library-use behavior and will facilitate them in designing better information literacy and user services programs.